2007
DOI: 10.1080/15368370701585490
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effects on Guinea Pig Serum: The Role of Free Radicals

Abstract: The present study was carried out to investigate the potential effects of ELF (extremely low frequency) electric field exposure on generating free radicals in guinea pigs. For this purpose, we determined thiobarbituric acid reactive substances (TBARS) levels, one of the byproducts of lipid peroxidation, the changes of the activities of superoxide dismutase (SOD), as an antioxidant enzyme, and gamma-Glutamyl transferase (GGT) as the key enzyme in GSH metabolism. Moreover, in order to investigate electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…Consistent with our results, Güler et al (2007) reported that there were no statistically significant changes for serum levels of TC, HDL-c, and TG between 50-Hz EF-exposed Guinea pigs and the controls. These findings were in accordance with those of another study that was conducted in static MF-exposed rats (Aida et al -2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our results, Güler et al (2007) reported that there were no statistically significant changes for serum levels of TC, HDL-c, and TG between 50-Hz EF-exposed Guinea pigs and the controls. These findings were in accordance with those of another study that was conducted in static MF-exposed rats (Aida et al -2013).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, another study reported that exposure to static MF for 5 days failed to alter plasma TC and TG levels, while exposure to static MF for 15 days increased plasma TC level, whereas decreased TG level (Lahbib et al 2010). Moreover, Güler et al (2007) reported that although increases were found in serum TC, LDL-c, and HDL-c of guinea pigs exposed to different intensities and directions of EF, these increment levels were not statistically significant with regard to controls. These data together with our results suggest that the effects on serum lipids are more significant in longer time periods of EMF exposure, and different frequencies, intensities, and durations of EMF exposure may have the different effects on serum lipids.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, several investigations were performed on free radical production and antioxidant system of the tissues and blood samples under the effects of magnetic fields (Lupke et al 2004;Zmyslony et al 2004;Bediz et al 2006;Simko et al 2006) and E fields (Harakawa et al 2005;Güler et al 2006, Güler et al 2007). Free radicals target structural molecules such as lipids, proteins and nucleic acids.…”
Section: Protein Oxidation Under Extremely Low Frequency Electric Fiementioning
confidence: 99%
“…Ozguner et al reported an increase in lipid peroxidation in rat heart following exposure to EMF [5]. Antioxidant defences and repair systems which help to protect cells against free radical destruction include superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) [6, 7]. There are several reports which indicate that exposure to EMF reduces antioxidant enzyme activities in rat tissues [8, 9].…”
Section: Introductionmentioning
confidence: 99%